IJABE remains to be included in 2014 Compendex Source List - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
IJABE remains to be included in 2014 Compendex Source List - Journals, according to the 2014 Compendex Source List effective as of 1 July 2014 issued by Elsevier at its website (http://www.elsevier.com/online-tools/engineeringvillage/ contentdatabase-overview). In the 2014 Compendex Source List - Journals, 4867 journals have been included in the new, with an increase of 1186 and 1331 journals compared with 3681 journals in 2013 Compendex Source List, and 3536 journals in 2012 Compendex Source List, respectively. In my estimation, there are 21 journals in agricultural-related areas in the 2014 Compendex Source List.